Smart villages in the EU and beyond - Visvizi, Anna 1976-; Lytras, Miltiadis D; Mudri, György (Emerald Publishing Limited, 2019)
Increasing depopulation is causing huge problems for rural communities, leading to a reduction in services and infrastructure in areas with ageing populations. This book examines the concept of the Smart Village, an ICT-conscious integrated strategy which provides a sustainable solution to these problems, helping to revitalize rural areas
Description based on publisher supplied metadata and other sources
Keywords: Europäische Union; Ländliche Entwicklung; Nachhaltigkeit; Electronic books; Aufsatzsammlung